ANALYSIS OF POLICY IMPLEMENTATION OF VOTER LIST UPDATING AT THE GENERAL ELECTION COMMISSION (KPU) NORTH GORONTALO REGENCY - Rahmola, Sophian M.; Mantali, Idham (Universitas Negeri Gorontalo, 2022)
In an effort to make the quality of the voter list, the KPU is obliged to ensure that all voters are registered on the final voter list (DPT) through the procedure for updating and compiling the voter list. The problem of quality & accuracy of the Permanent Voter List (DPT) is the responsibility of all election stakeholders such as KPU, Ministry of Home Affairs, Ministry of Foreign Affairs & active participation of all elements of society. This study aims to identify and analyze the implementation of the voter list updating policy at the General Election Commission (KPU) of North Gorontalo Regency. The research design was made in a qualitative narrative, using in-depth interview techniques in order to understand the process of implementing the voter list updating policy so that the voter list updating process at the KPU in North Gorontalo Regency. The results of the study explain that the implementation of the voter list updating policy is carried out using examples of policy implementations that can claim the complexity of cases to be resolved through certain policies, for example the Donald Van Meter Model using Carl Van Horn, Daniel Mazmanian & Paul A. Sabatier & Hogwood & Gunn Models.